Evaluation of Scrotal Temperature in Different Testicular Shapes by Infrared Thermography in Braford Bulls - Favaro, Patrícia da Cruz; Pereira, Gabriel Ribas; Barca Jr., Flávio Antônio; Seneda, Marcelo Marcondes; Alves Assunção, Augusto César; da Silva, Ivis Dias; Victalina Franco, Elis Maria; Gonçalves Galdioli, Victor Hugo; Kotz Jr., Celso (Acta Scientiae Veterinariae, 2019)
Background: The mechanisms of testicular thermoregulation may influence the blood flow provided by the testicular artery, where the proper blood supply to the testicle is crucial for promotingspermatogenesis and reproductive function in bulls. The size and shape of the testicles are determined by genetic mechanisms and environmental effects. A better understanding of the relationships between the anatomical characteristics of the testicles and scrotum can support a better reproductive assessment. The purpose of the current study was to evaluate the testicular temperature of different scrotal shapes using infrared thermography in bulls. Materials, Methods & Results: We evaluated 132 Braford bulls with an average age of 24 months. The evaluation of breeding bull semen was performed prior to the beginning of the experiment. Then, animals were selected on the basis of the size of their testes, which was determined by dividing the average width by the average length. The scrotal circumference was measured with a millimeter tape positioned around the largest circumference. Testicular and ocular temperature measurements and analysis were conducted using an infrared thermal camera, Flir T440 with emissivity of 0.98 and thermal sensitivity of 0.05°C. Testicular scrotum temperature and testicular shape were analyzed with one-way ANOVA using Minitab 16, and values of P < 0.05 were considered statistically significant. We observed that 67.42% of testicle shapes were long-oval, and 32.58% were long-moderate. The testicular temperature was higher in bulls with the long-moderate shape compared to those with the long-oval shape (P < 0.05). The mean length was higher in long-moderate shaped testicles compared to those of the long-oval shape (P < 0.01). There was no significant differences in rectal and ocular temperatures or in scrotal circumference between bulls with long-moderate and long-oval shapes (P > 0.05). In addition, the mean width was lower in testicles of long-moderate shape compared to those of the long-oval scrotal format (P < 0.01). Discussion: The results obtained showed that Braford bulls with the long-moderate testicular shape have a higher testicular temperature to maintain proper thermoregulation. The present study demonstrated that IRT can be used to evaluate the testicular temperature in animals with different scrotal conformations. In this study, Braford bulls showed lower length and width values for animals having long-moderate (9.21 and 5.22, respectively) and long-oval formats (8.56 and 5.56, respectively). In contrast, previous reports examining Nellore bulls between the ages of 17-20 months found a predominance of the long oval shape followed by the long-moderate shape, which indicates a change in testicular shape as age progresses, resulting in a rounder testicular shape. Perhaps other factors, such as the external cremaster muscle and tunica dartos, cause the testicles to be retracted towards the body at lower temperatures while at high temperatures, relaxation occurs. The prevailing testicular shape in Braford animals with a mean age of 24 months was the long-moderate shape. Thus, testicles with a larger surface area will have lower temperatures because they can dissipate heat more easily than testicles with lower surface area. The results suggest that the long-moderate scrotum format may influence the testicular temperature in mature Braford bulls.